2019
DOI: 10.25259/sni-213-2019
|View full text |Cite
|
Sign up to set email alerts
|

Skull base chordoma treated with proton therapy: A systematic review

Abstract: Background: Chordoma located in the skull base is usually a challenging surgical condition. It is often not possible to achieve gross total resection. Residual tumors have been treated with adjuvant focal radiation therapy employing high-energy particles most commonly through proton beam. In this review, we systematically analyzed indications and outcomes of this treatment with respect to local control rates of the lesion and factors determining recurrence of skull base chordomas. In addition, we collected dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…There is ongoing research regarding prognostic factors and optimal post-surgical radiation strategies with further evaluation needed regarding tumor biology and PBT versus radiosurgery. 13,14 Despite continuing improvements of surgical techniques, there is still considerable variation in the literature as to the optimal management technique. As such, we decided to perform a systematic review of surgical management in clival chordomas, particularly focusing on open versus endoscopic surgery with the aim to compare this against our own 10-year clinical experience of clival chordomas at our regional skull base unit in London (January 2009-October 2019) along with a couple of highlighted cases.…”
mentioning
confidence: 99%
“…There is ongoing research regarding prognostic factors and optimal post-surgical radiation strategies with further evaluation needed regarding tumor biology and PBT versus radiosurgery. 13,14 Despite continuing improvements of surgical techniques, there is still considerable variation in the literature as to the optimal management technique. As such, we decided to perform a systematic review of surgical management in clival chordomas, particularly focusing on open versus endoscopic surgery with the aim to compare this against our own 10-year clinical experience of clival chordomas at our regional skull base unit in London (January 2009-October 2019) along with a couple of highlighted cases.…”
mentioning
confidence: 99%
“…In contrast, postoperative radiotherapy is suggested for most patients with chondrosarcomas and chordomas as complete resection of the tumor is difficult and recurrent tumors are associated with poorer prognosis (84,85). Proton-beam therapy may be particularly useful as photon therapy is associated with a high rate of local failure and carries a significant risk of brainstem and cranial nerve damage (187)(188)(189).…”
Section: Malignant Tumors Of Bone and Cartilagementioning
confidence: 99%
“…76 Another review conducted in 2018 concluded that despite advances in proton therapy, recurrence rates in skull base chordoma remain high. 77 Large case series demonstrated that unfavorable tumor control was often linked to high residual volumes (>23 cm 3 ) and brainstem involvement. [78][79][80] Authors recommended that due to the radioresistant behavior of this neoplasm, a delivery of a dose of at least 74 Gy (RBE) to the tumor bed and other sites of gross disease is recommended.…”
Section: Biology Of Proton Beam Therapymentioning
confidence: 99%